2019
DOI: 10.1111/raq.12336
|View full text |Cite
|
Sign up to set email alerts
|

Salmon farming vulnerability to climate change in southern Chile: understanding the biophysical, socioeconomic and governance links

Abstract: Here, we describe an assessment of climate‐change vulnerability for the salmon farming sector in southern Chile using a model that combines semi‐quantitative measures of Exposure (risks), Sensitivity (economic and social dependence) and Adaptation Capacity (measures that prevent and mitigate impacts). The evaluation was carried out in eight pilot communes representative of salmon production (marine grow‐out). Exposure was estimated with a semi‐quantitative risk assessment tool based on oceanographic, meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 18 publications
0
41
0
4
Order By: Relevance
“…It has also been suggested that the main impact from climate change to the Chilean salmon industry could come from the rise of salinity in estuarine areas, which could affect salmon productivity and mortality (Gobierno de Chile , Soto et al . ; this special issue).…”
Section: A Brief Description Of the Structure And Socio‐economic Relementioning
confidence: 95%
“…It has also been suggested that the main impact from climate change to the Chilean salmon industry could come from the rise of salinity in estuarine areas, which could affect salmon productivity and mortality (Gobierno de Chile , Soto et al . ; this special issue).…”
Section: A Brief Description Of the Structure And Socio‐economic Relementioning
confidence: 95%
“…Some water bodies such as the Reloncaví estuary have a very large number of farms which generate risks for salmon production and for the ecosystem (Soto et al . ). As water bodies capacities are estimated individually (site by site) and not in broader spatial scales, no sound estimates of carrying capacity at fjords/channels scale are available.…”
Section: Salmon Farming Environmental Impacts During the Marine Fattementioning
confidence: 97%
“…Between 2011 and 2016, approximately 32% of marine fattening farms were located in sites strongly influenced by freshwater, brackish waters and estuaries (Soto et al . ). For the near future, General Circulation Models (GCM) forecast a reduction in precipitation in northern Patagonia (Garreaud ), which could favour sea louse proliferation.…”
Section: Salmon Farming Environmental Impacts During the Marine Fattementioning
confidence: 97%
See 2 more Smart Citations